Comparing the effect of in our own voice-family with psychoeducation on stigma in families of schizophrenia patients - Saeed Vaghee; Azam Salarhaji; Nastaran Vaghei (Tehran University of Medical Sciences, 2016)
Background & Aim: Families of patients with schizophrenia face with stigma as the most challenging psychosocial pressure; due to its negative consequences on mental health of family and important role of family in a treatment of these patients, it is considered as important mental health issues. Comparing the effect of In Our Own Voice-family with psychoeducation on stigma in the families of patients with schizophrenia. Methods & Materials: A total of 90 caregivers of patients with schizophrenia who hospitalized in Ibne-Sina Hospital of Mashhad have been selected randomly, and they have been placed in three groups of In Our Own Voice-family (in accordance with the National Union of standard list of psychiatric diseases), psycho education (according to Falloon et al. educational model) in two sessions of 4 hours, and control (without intervention). Data have been obtained by The Modified Version of the Internalized Stigma of Mental Illness scale (immediately before intervention and 1 month after intervention). Data were analyzed by SPSS software and ANOVA and t-test. Results: An average score of stigma reduced significantly In Our Own Voice-family in comparison with psychoeducation group (P < 0.001). However, the results were different in various subscales of stigma. So that, there was no significant difference between In Our Own Voice-family group and psychoeducation in terms of average crossovers of alienation subscale and stereotype endorsement after intervention (P > 0.050). However, In Our Own Voice-family group indicated significant reduction in comparison with psychoeducation in terms of subscales changes of discrimination experience and social withdrawal after intervention (P < 0.050). Conclusion: According to the effects of In Our Own Voice-family on reducing stigma in individual and social aspects, it is recommended to psychiatric nurses and nurses who work in psychiatric parts to use this method to reduce stigma among families with the psychiatric patients.